The Meaning of al-Maysir from the Perspective of Middle Eastern Mufasirs and Its Contex: English - Maliha, Dewi; Alhusna, Mahdalina Nanda (مجلة النور الدولية للقرآن والحديث, 2024)
This paper examines the perspectives of Sayyid Quṭb, Aḥmad Muṣṭafā al-Marāghī, Muḥammad ‘Abduh, and Wahbah al-Zuḥaylī regarding the meaning of al-maysir and its contextualization in contemporary settings. The study stems from the issue of modern prize-based draws, which share characteristics with the concept of al-maysir. The research aims to present a balanced interpretation to address these challenges. It explores the relationship between prize-based draws and al-maysir as outlined in Surah al-Baqarah [2]: 219 and Surah al-Mā’idah [5]: 90-91. A thematic tafsir approach is employed to capture the exegetical views, gathering related verses under a single theme for comprehensive analysis. The findings indicate that, according to Sayyid Quṭb, Aḥmad Muṣṭafā al-Marāghī, Muḥammad ‘Abduh, and Wahbah al-Zuḥaylī, not all forms of prize-based draws are deemed haram from a Quranic perspective. As technology has evolved, prize-based draws manifest in various forms, offline and online. The study concludes that draws associated with al-maysir—particularly those involving betting, fostering enmity, or causing negligence of religious duties—are impermissible. Among these exegetes, only Muḥammad ‘Abduh, in Tafsir al-Manār, specifically discusses maysir al-yanāṣīb, or lottery gambling, which closely resembles modern prize-based draws. Although contemporary draws may occur without direct interaction and may seem less prone to causing animosity compared to pre-Islamic gambling practices, they still involve elements of gambling as they represent the unjust acquisition of wealth without legitimate exchange or benefit.